A report on the practice in industry in fish culture - Angeles, Hilarion G. (College of Fisheries, 1950)
The different stations under the Bureau of Fisheries which I was tentatively assigned to apply the knowledge that I have acquired, learned and gained during my past two years of studies. The places where I was detained was firstly Tanay, Rizal was in a great improvements. This is due to our supreme technicalities our industriousness and the willingness to work, that is from clearing to beautification of the fishpond as well as the station. We have already done lot. Gourami are growing rapidly, due to the instructions that have been applied by us and other personnel. In the case of Dagat-dagatan you could expect a 100ppt improvements because of the magnificent work exerted by our energetic Head in Fish Culture, Mr. Herminio Rabanal, with the assistance of the members of the staff as well as the students and labourer of that station. Balayan, Batangas where I was lastly assigned to help and observe the way how they handle and manage the fishpond. The pond are not properly handled because the bantays lack sufficient tactics, methods and information regarding bangos culture. On our stay there we have given them a lot of instruction to be followed in the management, construction and other work to be done. The primitive methods that they are using have been replaced by modern one which we have insisted to follow. If they could follow in full the modern methods that we have applied I think their business will be in success to have a better production.